2000
DOI: 10.4049/jimmunol.165.1.573
|View full text |Cite
|
Sign up to set email alerts
|

CTL Control of EBV in Nasopharyngeal Carcinoma (NPC): EBV-Specific CTL Responses in the Blood and Tumors of NPC Patients and the Antigen-Processing Function of the Tumor Cells

Abstract: Undifferentiated nasopharyngeal carcinoma (NPC) is latently infected with EBV and expresses a restricted number of viral proteins. Studies in healthy virus carriers have demonstrated that at least some of these proteins can act as targets for HLA class I-restricted CTLs. Therefore we have explored the possibility of a CTL-based therapy for NPC by characterizing EBV-specific CTL responses in 10 newly diagnosed NPC cases and 21 healthy virus carriers from Southeast Asia. Using the autologous EBV-transformed lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 51 publications
2
84
1
Order By: Relevance
“…To date, conventional approaches for the treatment of EBVrelated malignancies are often not curative or associated with serious complications. New immunotherapeutic strategies, such as adoptive transfer of CTLs or mAbs, may be effective if the tumor cells express immunodominant proteins (25,27,38). HD, BL, and NPC cancers appeared to be less susceptible to immunotherapeutic intervention, presumably due to the expression of a more restricted array of subdominant EBV-encoded epitopes derived from latent proteins (EBNA1, LMP1, and LMP2) (19,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, conventional approaches for the treatment of EBVrelated malignancies are often not curative or associated with serious complications. New immunotherapeutic strategies, such as adoptive transfer of CTLs or mAbs, may be effective if the tumor cells express immunodominant proteins (25,27,38). HD, BL, and NPC cancers appeared to be less susceptible to immunotherapeutic intervention, presumably due to the expression of a more restricted array of subdominant EBV-encoded epitopes derived from latent proteins (EBNA1, LMP1, and LMP2) (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…NPC patients possessed CTL precursors specific for EBV-LMP2 and EBV-specific T cell responses were detectable in patients, albeit at lower levels than in healthy controls (26,27). The point was whether they included responses to those viral proteins expressed in the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…25 However, it has also been demonstrated that EBV positive NPC tumor cells could be recognized by autologous EBV specific CTLs in vitro; and the antigen proceeding and presenting system is intact in NPC tumor cell lines in previous research. 60,61 These founding provide the possibility of success for immunotherapy in some NPC patients who have intact antigen proceeding and presenting systems in tumor cells. However, it is necessary to examine the expressions of immune-molecules in tumor lesions, which will influence the outcome of T-cell-based adoptive immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 However, these tumors show patterns of viral antigen expression, which appear to be limited to EBNA1, LMP1 and LMP2. Since endogenously expressed EBNA1 is protected from presentation via the HLA class I pathway, attempts to target these tumors with EBV-specific CTLs depend upon the ability to boost responses to LMP1 and LMP2.…”
Section: Discussionmentioning
confidence: 99%